2007
DOI: 10.1016/j.dsr2.2007.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved iron in the vicinity of the Crozet Islands, Southern Ocean

Abstract: The annual phytoplankton bloom occurring north of the Crozet Plateau provides a rare opportunity to examine the hypothesis that natural iron fertilisation can alleviate HNLC conditions normally associated with the Southern Ocean. Therefore, during CROZEX, a large multidisciplinary study performed between November 2004 and January 2005, measurements of total dissolved iron (DFe, 0.2 m) were made on seawater from around the islands and atmospheric iron deposition estimated from rain and aerosol samples. waters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 67 publications
8
139
1
Order By: Relevance
“…These values indicate that neither dissolved nor particulate iron penetrate far into open ocean in the latitudinal/meridional direction when the main current is parallel to the coast. Our estimate of SL DFe (25 km) is identical to the SL DFe found by Planquette et al (2007) and is comparable to the SL DFe (16 km) found by Johnson et al (1997) for Monterey Bay. However, much higher values for SL DFe were estimated for near-shore waters off the Kerguelen Islands (151 km; Bucciarelli et al, 2001) and near the Galapagos Islands (103 km; Gordon et al, 1998).…”
Section: Scale Lengths Of Fe Transportsupporting
confidence: 77%
See 1 more Smart Citation
“…These values indicate that neither dissolved nor particulate iron penetrate far into open ocean in the latitudinal/meridional direction when the main current is parallel to the coast. Our estimate of SL DFe (25 km) is identical to the SL DFe found by Planquette et al (2007) and is comparable to the SL DFe (16 km) found by Johnson et al (1997) for Monterey Bay. However, much higher values for SL DFe were estimated for near-shore waters off the Kerguelen Islands (151 km; Bucciarelli et al, 2001) and near the Galapagos Islands (103 km; Gordon et al, 1998).…”
Section: Scale Lengths Of Fe Transportsupporting
confidence: 77%
“…However, much higher values for SL DFe were estimated for near-shore waters off the Kerguelen Islands (151 km; Bucciarelli et al, 2001) and near the Galapagos Islands (103 km; Gordon et al, 1998). These differences were attributed to different water circulation patterns in those coastal systems and the difference between the respective surface areas of the islands (Planquette et al, 2007). Geochemical characteristic of the source area, type of continental shelf and margin, and differences in the biological processes might also play some role.…”
Section: Scale Lengths Of Fe Transportmentioning
confidence: 98%
“…As previously measured around South Georgia (Nielsdóttir et al, 2012, Holeton et al, 2005, but also in other regions of the Southern Ocean (e.g. Ardelan et al, 2010;Bucciarelli et al, 2001;Planquette et al, 2007), the model depicts highest dFe concentrations in near-shore waters (> 5 nM), decreasing with distance from the island. Our model results clearly show that the South Georgia island mass effect can reach regions located far away from the island (> 1000 km), where dFe concentrations may still be above background concentrations.…”
Section: The South Georgia Island Mass Effectsupporting
confidence: 51%
“…Stations M10 and M5 are located in the PFZ . Altimetry data suggest station M6 might be seasonally influenced by a weakly marked Polar Front (Park et al, 1993;, but the presence of a temperature minimum layer (1.6°C at 200 m) strongly supports its belonging to the AAZ (Pollard et al, 2002;Planquette et al, 2007;Salter et al, 2014). Statistical differences in minimum diameter (d min ) and size-normalized weight (SNW) between the four study sites were tested for three species independently (N. pachyderma, T. quinqueloba, G. bulloides) using a non-parametric Kruskall-Wallis test.…”
Section: Test Size and Size Normalized Weight Comparison With Assemblmentioning
confidence: 99%